Experimental Investigation on the Effect of Steel Fibers on the Flexural Behavior and Ductility of High-Strength Concrete Hollow Beams - Ahmmad Abbass; Sallal Abid; Mustafa Özakça (Advances in Civil Engineering)
In this study, an experimental work was directed toward comparing the flexural behavior of solid and hollow steel fiber-reinforced concrete beams. For this purpose, eight square cross-sectional beam specimens, four solid and four hollow, were prepared. One concrete mixture with four different steel fiber contents of 0, 0.5, 1.0, and 1.5% were used. The side length of the central square hole was 80 mm, whereas the cross-sectional side length was 150 mm. All beams were tested under four-point monotonic loading until failure. In addition to the solid and hollow beams, cylinders were cast to evaluate the compressive strength, splitting tensile strength, and modulus of elasticity, whereas prisms were used to conduct the fracture test. The test results showed that all fibrous beams failed in flexure, whereas those without fiber exhibited flexural-shear failure. In general, the flexural behavior of fibrous-beams was superior to that of beams without fiber. The hollow beams with fiber contents of 0, 0.5, and 1.0% were observed to withstand lower loads at cracking, yielding, and peak stages compared with their corresponding solid beams; this was not the case for the 1.5% fiber hollow beam, which exhibited a higher peak load than its corresponding solid beam. Although all eight beams exhibited ductility indices higher than 3.7, hollow beams exhibited better ductility than solid beams, showing higher ductility index values.